Global Challenges of Being a Strength Athlete during a Pandemic: Impacts and Sports-Specific Training Considerations and Recommendations - Christopher Latella; G. Gregory Haff (MDPI AG, 2020)
The ongoing global pandemic brought about by Coronavirus II (SARS-Cov-2 or COVID-19) has caused an ongoing cessation of sporting competitions and training facility closures. This is a fundamental challenge for amateur and elite sporting professionals. Although recommendations have been provided for team-sport athletes to maintain general and sport-specific conditioning, these methods are often not optimal for strength athletes (i.e., powerlifting (PL) and weightlifting (WL)) due to the unique and narrow set of performance requirements posed by these sports. The purpose of this review is to provide evidence-based information and recommendations and highlight potential strategies and approaches that may be used by strength (PL and WL) athletes during the current global crisis. Collectively, we provide evidence from resistance training literature regarding the loss of muscle strength, power and mass, minimum training frequencies required to attenuate such losses and training re-adaptation. Additionally, we suggest that time off training and competition caused by ongoing restrictions may be used for other purposes, such as overcoming injury and improving movement quality and/or mobility, goal setting, psychological development and emphasizing strength sports for health. These suggestions are intended to be useful for coaches, strength athletes and organizations where existing training strategies and recommendations are not suitable or no longer feasible.